Digital distinctions: mechanisms of difference in digital media use - Bengtsson, Stina (MedieKultur: Journal of media and communication research, 2015)
This article aims at understanding to understand the distinctive mechanisms of digital media use, seen in relation to cultural practices at large. The empirical material is a survey study of university students at the Business Administration, Media and Communication Studies, Political Science and Philosophy departments at Södertörn University, Sweden. The empirical analysis deals with the students’ digital media use and preferences, and how these are related to their broader cultural practices and preferences. Specific attention is paid to the webpages the students mention in the survey, and how these are distributed among the groups. By showing detailed information on these areas, the mechanisms of difference of digital media use are revealed.